The Federated States of Micronesia - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
The Federated States of Micronesia (FSM) remains at high risk of debt distress under the Debt Sustainability Framework (DSF). Unless the compact agreement with the United States or parts of it are renewed, the FSM will face a fiscal cliff when the U.S. Compact grants amounting to 20 percent of gross domestic product (GDP) are expected to expire in FY2023. Under the baseline scenario without fiscal adjustments, the fiscal cliff would put debt on an upward trajectory starting in FY2024, with the external debt-to-GDP ratio reaching 30 percent in FY2029 and 57 percent in FY2039, and the public debt-to-GDP ratio reaching 43 percent in FY2029 and 67 percent in FY2039. As a result, the DSF thresholds on the present value of external debt-to-GDP and public debt-to-GDP ratios are projected to be breached within a 20-year horizon. While mechanical application of the DSF based on a 10-year forecast horizon would imply a moderate risk rating, the envisaged breach of the thresholds within a 20-year forecast horizon would warrant an assessment of high risk of external and overall debt distress. Lowering the risk of debt distress would require a fiscal adjustment and steadfast structural reforms to promote private sector growth. The FSM’s vulnerability to climate change and weather-related natural disasters constitutes a major risk and calls for strategies to strengthen climate change resilience